2018
DOI: 10.1002/mbo3.617
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane growth and nutrition levels are differentially affected by the application of PGPR and cane waste

Abstract: Mineral and organic fertilization can be optimized by using rhizobacteria which increases dry matter, yield, and nutrients in the soil and plant, among the other biological inputs. However, the discovery of single microbes or a consortium that can benefit plants has been a challenge. In this context, this study aimed to evaluate the effects of Bacillus subtilis and Bacillus pumilus combined with mineral fertilization and sugar and alcohol industry by-products in presprouted and the initial growth phase of suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…In recent years, plant growth-promoting bacteria (PGPB) have attracted increasing attention because they promote the growth of crops such as maize, rice, and sugarcane (Almaghrabi et al, 2014;Prittesh et al, 2017;Santos et al, 2018). The application of one or more PGPB strains to fields enhanced the growth of crops while reducing the need for chemical fertilizers (Adesemoye et al, 2009), thereby representing a beneficial approach to more sustainable agricultural practices.…”
mentioning
confidence: 99%
“…In recent years, plant growth-promoting bacteria (PGPB) have attracted increasing attention because they promote the growth of crops such as maize, rice, and sugarcane (Almaghrabi et al, 2014;Prittesh et al, 2017;Santos et al, 2018). The application of one or more PGPB strains to fields enhanced the growth of crops while reducing the need for chemical fertilizers (Adesemoye et al, 2009), thereby representing a beneficial approach to more sustainable agricultural practices.…”
mentioning
confidence: 99%
“…Among the advantages of PSS system are quality and vigor control, greater homogeneity of seedlings and optimization of water and nutritional resources. Several studies have already described the beneficial effect of bacterial inoculants on sugarcane development (Kleingesinds et al 2018;Marcos et al 2016;Santos et al 2018;Silveira et al 2018), but the present study is the first to evaluate the benefit of plant-microorganism interactions with PGPB and AMF on sugarcane PSS focused in growth promoting and nutritional improvement. The evaluation of these beneficial microorganisms on sugarcane development can direct future studies on the inoculant recommendations for sugarcane PSS.…”
Section: Soil and Plant Nutrition Articlementioning
confidence: 99%
“…These results revealed a combination of Azospirillum brasilense and Bacillus subtilis allied to the low cost of P 2 O 5 was the best fertilizers management in the sugarcane which is meaningful production practice of sugarcane. Santos et al (2018) reported that the use of B. subtilis together with by-products can improve soil fertility parameters and decrease adverse effects associated with vinasse fertilization, in addition to providing shoot and root growth and providing collective synergy for high yield of sugarcane production with environmental benefits. Moura et al (2018) have shown that the use of Azospirillum in sugarcane crop improved root system leading to better water and nutrient uptake that in turn may influence yield positively.…”
Section: Pgpr Used In Sugarcanementioning
confidence: 99%